PENERAPAN APLIKASI CRM UNTUK CAREER CENTRE PADA PERGURUAN TINGGI IBI DARMAJAYA - Sri Karnila (IIB Darmajaya, 2012)
IBI Darmajaya as colleges can also apply CRM to improve customer management at institutions like corporate training center. IBI Darmajaya training center providing information related to training, also play a role as ‘career centre’ that bridges the corporate and college alumni. Alumni and partner companies or companies which alumnus absorb the labor force, either working together or not, is a customer that receiving IBI Darmajaya services about training and job information. Career centers currently provide training and job information on the alumni that still taking education or a student and only with companies that work together. This allows the service as well as the connection between alumni, companies and IBI Darmajaya less effective, because the information provided by the career center is not necessarily known to the alumniand even the partnerscompany. That requires a CRM application at the career center, so that IBI Darmajaya have yielded information communication media according to the needs of alumni and companies. Expected later this process can foster sustainable relationships between alumni and companies - companies with higher education.Keywords : Perguruan Tinggi, CRM, career centre,